A Constructivist Analysis of the Establishment of the AUKUS Security Pact and its Implications for Regional Stability in the Indo-Pacific - Johni R.V. Korwa; Meyland S. F. Wambrauw (Universitas Airlangga, 2023)
This article attempts to shed light on AUKUS formation based on constructivist perspective and its implications for regional stability in the Indo-Pacific. Using a qualitative approach with a case study method, this article found that the formation of AUKUS is strongly influenced by two fundamental elements of constructivism: identity and interests. Identity refers to the shared ideas among the Anglo-Saxon nations (including Canada and New Zealand). Nevertheless, New Zealand tends not to join AUKUS due to its commitment to non-proliferation, while Canada seems to contribute nothing to the nuclear submarine program. The interests of the AUKUS alliance are: the US desires to strengthen its hegemony in the Indo-Pacific and rebalance China’s domination; the UK craves to become the first European country to enhance alliance cooperation in the Indo-Pacific after Brexit; and Australia’s willingness to modernize its military capability and affirms its commitment to which allies it counts on in the future. The implications of establishing AUKUS might include: undermining the status quo in the region concerning a nuclear-free zone, weakening existing cooperation agreements and reducing mutual trust between traditional allies, and bringing catastrophe to the region by triggering an armed race. Keywords: AUKUS; China; Constructivism; Indo-Pacific; Regional Stability